2007
DOI: 10.1210/en.2007-0859
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Concentration of 17β-Estradiol on Sympathetic Reinnervation in Ovariectomized Infarcted Rats

Abstract: 17beta-Estradiol (E2) has been shown to exert antiarrhythmic effect after myocardial infarction; however, the mechanisms remain unclear. This study was performed to determine whether E2 exerts beneficial effects through attenuated sympathetic hyperreinnervation after infarction. Two weeks after ovariectomy, female Wistar rats were assigned to coronary artery ligation or sham operation. Twenty-four hours after coronary ligation, rats underwent one of five treatments: 1) sc vehicle treatment (control), 2) sc E2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
6
1
Order By: Relevance
“…These results are in agreement with several other studies that have shown estrogen levels and uterine weight decrease after ovariectomy [52][53][54]. This study also showed that sarcolemmal ERα expression was markedly increased in ventricular tissue from ovariectomized mice (6-weeks post-surgery).…”
Section: Sshrs and Hormonal Variationssupporting
confidence: 93%
“…These results are in agreement with several other studies that have shown estrogen levels and uterine weight decrease after ovariectomy [52][53][54]. This study also showed that sarcolemmal ERα expression was markedly increased in ventricular tissue from ovariectomized mice (6-weeks post-surgery).…”
Section: Sshrs and Hormonal Variationssupporting
confidence: 93%
“…Considering that the half-life of testosterone is much shorter than that of E 2 , and that testosterone was measured 1 day after MT injection, it is not surprising that no amount of testosterone was detected in GNX + MT female rats. The plasma E 2 level (170 pg/ml) in the control GNX ( table 3 ) appeared to be high, compared to that (about 19 pg/ml) found in another study [11] . Although the plasma E 2 level was high, the uterine weight (500 mg/kg BW) seems to be comparable to others [12] .…”
Section: Discussioncontrasting
confidence: 57%
“…While the present study provides strong evidence that sympathetic hyperinnervation requires increased numbers of macrophages, additional studies with larger numbers of rats and a more protracted time course will be required to assess any impact of clodronate liposome treatment on post-infarct survival. Similarly, the extent to which other factors reported to modulate infarct sympathetic hyperinnervation, which include estrogen [33], statin treatment [32], and glucocorticoids [14], affect macrophage dynamics and NGF expression remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%